Innovative Opportunities of Artificial Intelligence in Educational Management Systems and its Practical Applications - Ubbiev Alisher Tayirovich; Bekbaev Gamzatdin Aleuatdinovich (Scientific Trends, 2025)
This article explores the innovative opportunities and practical applications of Artificial Intelligence (AI) in educational management systems. It examines how AI technologies contribute to improving the quality of education by optimizing administrative processes, enhancing personalized learning, and supporting data-driven decision-making. The article concludes that AI is a powerful instrument for transforming modern education. Although challenges such as financial costs, teacher training, and data privacy remain, the benefits of AI integration — efficiency, adaptability, and innovation — make it an indispensable part of future educational management systems.
Keywords: Artificial intelligence; educational management; adaptive learning; automated assessment; virtual assistants; innovation in education; digital transformation.